Study on some patient characteristics, satisfaction, pattern of utilization and cost for magnetic resonance image scanning at the Neurosurgical Unit. National Hospital of Sri Lanka - Sarathchandra, A.W (My University, 2008)
Knowledge regarding some aspects of MRI scanning was assessed by a self-administered questionnaire given to the medical officers of the relevant wards. Patient details were collected using interviewer-administered pre- tested questionnaires. There was a nonresponse of 20 percent due to patients being unconscious out of a sample size of 403 patients. The majority of patients were females and in the age category of 30-49 years. Three-quarters of patients were satisfied with the duration of hospital stay till the scan date. The waiting time outside the MRI room is one to two hours in more than half the patients. Patient satisfaction with regard to communication was very high and this was much more with respect to the MRI unit staff than ward staff.